From relation to the field: Modes of unconscious fantasy elaborations. (2nd October 2019) - Celenza, Andrea
Abstract: Relational and field theories have much in common, despite divergent foundations. In this paper, several areas of divergence are selected, including the structure of the field as a relational matrix or as an unconscious joint fantasy of the couple; the fate and form of insight; and the nature of the unconscious as relational or ubiquitous. Differences in cognitive and attentional sets are identified and linked to different modes of insight. Using a clinical vignette, these divergences will be illustrated with an attempt to compare and contrast the two approaches through a discussion of how each lens highlights, expands, or forecloses different features of the analytic process. A mode of conceiving the unconscious as unstructured and multiple in potential is offered to reconcile divergent assumptions in therapeutic action. A consideration of Sandor Ferenczi's clinical emphasis on relaxed technique, elasticity, and especially mutuality suggests that he would have been a field theorist were he among us today.